2015
DOI: 10.1039/c5tc02274f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single atom substitution in benzochalcogendiazole acceptors on the performance of ternary memory devices

Abstract: Ternary memory storage performances of three benzochalcogendiazole derivative based devices clearly demonstrate the effect of single atom substitution on the molecular planarity, film morphologies and device threshold voltages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 70 publications
2
32
0
Order By: Relevance
“…It demonstrated that the devices of TPA‐based PIs possessed lower energy consumption. And PIs containing TPA moieties decreasing the energy band gap effect were better than containing Cz moieties in this polymer system, it was in accordance with the result of UV–vis absorption spectra, this could be more beneficial to CT by microstructure . The devices of the fabricated PI(TPA‐TPF PMDA), PI(TPA‐TPF BPDA), and PI(Cz‐TPF PMDA) had a characteristics of low misreading rate, due to their ON/OFF current ratios beyond 10 3 .…”
Section: Resultssupporting
confidence: 76%
“…It demonstrated that the devices of TPA‐based PIs possessed lower energy consumption. And PIs containing TPA moieties decreasing the energy band gap effect were better than containing Cz moieties in this polymer system, it was in accordance with the result of UV–vis absorption spectra, this could be more beneficial to CT by microstructure . The devices of the fabricated PI(TPA‐TPF PMDA), PI(TPA‐TPF BPDA), and PI(Cz‐TPF PMDA) had a characteristics of low misreading rate, due to their ON/OFF current ratios beyond 10 3 .…”
Section: Resultssupporting
confidence: 76%
“…[6] However, an intrinsically methodologicalf law exists in the above molecular-tuning studies:i nm osto ft hese works, the structural change in the molecule was too large and caused changes in many electronic (donor-acceptor numbers,H OMO-LUMO levels,a nd gaps), geometric (planarity and conjugation length), and intermolecular (stacking manner and strength) properties simultaneously.T hese complex variations may cause unnecessary confusion when attempting to correlate as ingle structural effect with macroscopic device performance. In this respect, single-atom substitution of the target molecule, which causes only an infinitesimalchange to the molecular structure, is arigorous way to study the structure-performance relationship in RRAMs.I ndeed, our group recently successfully appliedt his single-heteroatom-substitution method to decrease the threshold voltages [7] and switch the storaget ype from dynamic RAM (DRAM) to static RAM (SRAM). [8] The mechanismsb ehind these results were also studied in depth,t hanks to the simple structural variation.H owever,s witching the memory level through single-atom substation,f or example, from binary to ternary,r emains challenging but very interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, numerous studies have explored new RRAM active materials based on the measurements on individual devices, but statistical data on a large batch are rarely reported. 4 Our recent statistical work 9,1113 demonstrated that the ternary memory yield of organic RRAMs is generally low (∼50%), despite the effectiveness of the molecular design in improving the ternary yield and switching voltage distributions. The frustration of material innovation has urged us to seek other strategies for improving device reproducibility.…”
mentioning
confidence: 99%
“…11,12 We collected the X-ray diffraction (XRD) patterns for the SA-Bu powder prior to the deposition and for the films deposited on the three types of ITO substrates (Fig. S9†).…”
mentioning
confidence: 99%